INFLUENCE OF CORPORATE SOCIAL RESPONSIBILITY (CSR) ON EMPLOYEES' WORK MOTIVATION: A DEVELOPING COUNTRY PERSPECTIVE - Khan, Uzair Abdullah; Ali, Uzma; Channa, Khalil Ahmed (APPS Publications, 2021)
This paper investigates the significance of the employee’s perspective in the context of corporate social responsibility, concerning its implications on employees’ motivation. We contend that our literature lacks an internal perspective beyond CSR’s universally recognized implications on external factors. This study aimed to explore the phenomenon and its internal implications on employees to add new knowledge in this domain and explore a developing country perspective, i.e., Pakistan. Besides, we hope to find a link/association between CSR and human resource management by exploring. So, the research may help HR managers in strategic formulation relating to workforce management, specifically CSR as a tool for employees’ motivation. Based on the McClelland’s framework of motivation – the need for affiliation, achievement, and power as an initial framework – we recognized the influence of CSR within the perspective of achievement and affiliation with no insinuation of power, grounded in our context. Moreover, in our empirical examination based on indepth interviews from Interior Sindh, spiritual obligations and self-actualization as in the purpose of life were two of the most confounding results inferred from our study. Besides, several subthemes emerged in our analysis, highlighting the underpinning process behind our main themes, i.e., how the sense of achievement in our study triggers the sense of loyalty, pride, and happiness among employees. The findings confirm that the main driving force behind organizational CSR is usually based on external factors (e.g., PR effect, government regulation, brand image, tax benefits) with rare emphasis on internal factors (e.g., effect on employees).